2015
DOI: 10.5535/arm.2015.39.5.667
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pulsed Radiofrequency Applied to the Peripheral Nerve in Chronic Constriction Injury Rat Model

Abstract: ObjectiveTo investigate the effect of pulsed radiofrequency (PRF) applied proximal to the injured peripheral nerve on the expression of tumor necrosis factor-α (TNF-α) in a neuropathic pain rat model.MethodsNineteen male Sprague-Dawley rats were used in the study. All rats underwent chronic constriction injury (CCI) procedure. After 7 days of CCI, withdrawal frequency of affected hind paw to mechanical stimuli and withdrawal latency of affected hind paw to heat stimulus were measured. They were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…The pain was mostly relieved on the 8 th day and it was almost completely relieved on the 14 th day. These results are consistent with those in previous studies 7 , 26 , 27 and confirm that PRF on an oppressed site of a peripheral nerve can gradually and significantly alleviate the hyperalgesia and allodynia of an NP model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pain was mostly relieved on the 8 th day and it was almost completely relieved on the 14 th day. These results are consistent with those in previous studies 7 , 26 , 27 and confirm that PRF on an oppressed site of a peripheral nerve can gradually and significantly alleviate the hyperalgesia and allodynia of an NP model.…”
Section: Discussionsupporting
confidence: 93%
“…The above-mentioned results indicated that PRF could inhibit the transcription and translation of CGRP in the rat's DRG. At present, no consensus on the analgesic mechanism of PRF has been reached, and it is believed that the mechanism might be related to the influences from a variety of neuropeptides, proteins, and inflammatory factors 26 , 27 , 39 , which may not be independent of each other. Moreover, what type of connection and which is the core part of the PRF role remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PRF was administered at 42°C, a standard setting, to the ligated sciatic nerves of CCI rats. As in previous studies, [10,17,18] mechanical allodynia and thermal hyperalgesia were significantly improved 7 days after treatment and further improved by day 14. However, this study included a longer follow-up period than previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Pulsed radiofrequency is a short intermittent pulse with 480 ms heat dissipation interval so that the temperature acting on the tissue does not exceed 42 • C. It does not cause nerve damage (Choi et al, 2014), only plays a role in neuromodulation (Lee et al, 2015). Therefore, PRF can act on the cervical nerve root for upper extremity PHN.…”
Section: Introductionmentioning
confidence: 99%